Use of Biphasic Continuous Positive Airway Pressure in Premature Infant with Cleft Lip-Cleft Palate - Lovya George; Sunil K. Jain (Thieme Medical Publishers, Inc., 2015)
Abstract Preterm infants (PIs) often require respiratory support due to surfactant deficiency. Early weaning from mechanical ventilation to noninvasive respiratory support decreases ventilation-associated irreversible lung damage. This wean is particularly challenging in PIs with cleft lip and cleft palate due to anatomical difficulties encountered in maintaining an adequate seal for positive pressure ventilation. PI with a cleft lip and palate often fail noninvasive respiratory support and require continued intubation and mechanical ventilation. We are presenting the first case report of a PI with cleft lip and palate who was managed by biphasic nasal continuous positive airway pressure.